ENGAGEMENT OF YOUTH STUDENTS IN HEALTHY MOVEMENT ACTIVITY: CHALLENGES AND OPPORTUNITIES NOWADAY (Physical Culture and Sport: Scientific Perspective, 2024)
Preserving and strengthening the health of the young generation is a priority for Ukraine. Unfortunately, the lifestyle of today's youth is "absolutely sedentary and connected to the virtual world of the Internet." Researchers point out a chronic lack of physical activity, which becomes a threat to the normal health and physical development of Ukrainian students. In the conditions of war, physical activity can also be a mean of relieving stress and strengthening the body.The purpose of the study is to analyze the current problem of involving student youth in health-recreational physical activity.The analysis of the scientific literature indicates the existence of different approaches to the involvement of youth in health and recreational activities. However, modernity makes new demands. The main reasons of the low level of involvement of Ukrainian student youth in physical activity are: the COVID-19 pandemic and the russian federation's war against Ukraine; serious backwardness of the domestic system of school and family physical education; long-term use of "coercion and intimidation" in the system of physical education of students; unattractive state of the material and technical base; dependence of education seekers on gadgets (smartphones, computers, etc.); low level of information and educational activities.The analysis of the existing practice of physical education in institutions of higher education shows that the current regulatory and legal mechanisms are not implemented with due efficiency. The modern domestic system of involving student youth in health-improving physical activity requires persistent and systematic work on the implementation of available opportunities to increase the efficiency of its functioning.The proposed promising directions for increasing the level of student involvement in health-improving motor activity can be implemented only on a scientific basis by consolidating the efforts and resources of all stakeholders.
Keywords: students; motor activity; health; involvement of youth; institution of higher education